Pengaruh Persepsi Harga, Kepercayaan dan Promosi Terhadap Minat Beli pada Situs E – Commerce Blibli (Survei Pada Pengguna Situs E-Commerce Blibli di Kabupaten Kuningan) - Gunawan, Wely Hadi; Hardiansyah, Indra; Fatmasari, Dewi (Indonesian Journal of Strategic Management, 2022)
This research was conducted on BliBli E-commerce Site Users in Kuningan Regency. The purpose of this study was to determine the perception of price, trust and promotion of buying interest (Survey of BliBli E-commerce Site Users in Kuningan Regency). The population in this study were 100 respondents, the sampling technique used was purposive sampling, the data collection method used a questionnaire, the data analysis technique used in this study was multiple linear regression analysis. The results of the test state that : Price perception has a positive and significant effect on buying interest, trust has a positive effect on buying interest, promotion has a positive effect on buying interest.